First Identification of Human Adenovirus Subtype 21a in China With MinION and Illumina Sequencers - Ye, Fuqiang; Han, Yifang; Zhu, Juanjuan; Li, Peng; Zhang, Qi; Lin, Yanfeng; Wang, Taiwu; Lv, Heng; Wang, Changjun; Wang, Chunhui; Zhang, Jinhai (Frontiers in Genetics, 2020)
Human adenoviruses (HAdVs) have been demonstrated to cause a diversity of diseases among children and adults. The circulation of human adenovirus type 21 (HAdV21) has been mainly documented within closed environments in several countries. Nonetheless, respiratory infections or outbreaks due to HAdV21 have never been reported in China. MinION and Illumina platforms were employed to identify the potential pathogen from a throat swab. Discrepancies between MinION and Illumina sequencing were validated and corrected via polymerase chain reaction (PCR). Genomic characterization and recombinant event detection were then performed. Among the 35,466 high-quality MinION reads, a total of 5,999 reads (16.91%) could be aligned to HAdV21 reference genomes (genome sizes ≈35.3 kb), among which 20 had a length of >30 kb. A genome sequence assembled from MinION reads was further classified as HAdV subtype 21a. Random downsampling revealed as few as 500 nanopore reads could cover ≥96.49% of current genome. Illumina sequencing displayed good consistency (pairwise nucleotide identity = 99.91%) with MinION sequencing but with 31 discrepancies that were further validated and confirmed by PCR coupled with Sanger sequencing. Restriction enzymes such as BamHI and KpnI were able to distinguish the present genome from HAdV21 prototype and HAdV21b. Phylogenetic analysis employing whole-genome sequences placed our genome with members only from subtype 21a. Common features among HAdV21a strains were identified, including polymorphisms discovered in penton and 100 kDa hexon assembly–associated proteins and a recombinant event in the E4 gene. Using MinION and Illumina sequencers, we identified the first HAdV21a strain from China, which could provide key genomic data for disease control and epidemiological investigations.